Preparation method of plastic wood-based filtering material for removing micro-plastics in water
By combining delignin treatment and EPTMAC modified wood, plastic wood-based filter materials that efficiently adsorb microplastics are prepared, and laminates are formed by hot pressing, which solves the problems of low adsorption efficiency and secondary pollution in existing wastewater treatment, and achieves efficient, economical and environmentally friendly microplastic removal effects.
Patent Information
- Application Number
- CN202411606239.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-12
- Publication Date
- 2025-04-08
AI Technical Summary
In the existing sewage treatment process, the adsorption efficiency is low and the cost is high, and the adsorbed micro-nanoplastics may be released to the environment again to form secondary pollution.
By treating wood with delignin, improving its hydrophilicity and plasticity, and combining with EPTMAC, plastic cationic wood is prepared as filter material to adsorb microplastics with electrostatic interactions, and laminates are formed by hot pressing to reduce the risk of desorption.
It significantly improves the adsorption efficiency of microplastics, reduces processing costs, and avoids secondary pollution of microplastics, improving the sustainability and mechanical properties of the material.
Smart Images

Figure CN119771357A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of microplastic adsorption materials, and specifically relates to a method for preparing a plastic wood-based filter material for removing microplastics in water. Background Art
[0002] The presence of microplastics has become an environmental problem that needs to be addressed urgently, especially plastic particles with a diameter of less than 1 micron, often referred to as nanoplastics. Although water treatment plants play an important role in treating water quality, they cannot completely remove microplastics in the water. Microplastics not only cause serious pollution to the ecological environment, but may also pose a threat to human health through the food chain, which makes it particularly important to develop technologies to efficiently remove microplastics.
[0003] At present, many methods for removing microplastics from the environment have some technical limitations, such as high cost, poor removal effect, and the possibility of generating other pollutants during the removal process. Among these methods, adsorption technology is considered to be a more ideal removal method. It has a simple process, relatively low cost, and has advantages in adsorption effect and broad-spectrum removal of microplastics. However, most microplastics have a negative charge on the surface in water, which requires the development of adsorbents with a positive charge on the surface so that they can effectively bind to microplastics through electrostatic interactions.
[0004] EPTMAC (solid active cationic etherifying agent) is a chemical substance that can react with cellulose. The generated cationic cellulose can be effectively used for the adsorption of microplastics in water. Wood itself has a unique hierarchical porous structure, the main component of which is cellulose. This structure not only gives wood many unique properties, but also provides a wide range of space for its modification and functionalization. By delignifying wood, the plasticity of wood is improved while the hydrophilicity of wood is improved and more active groups are exposed. Combining delignified wood with EPTMAC to prepare materials for microplastic adsorption can not only improve the removal effect of microplastics, but also broaden the functional application prospects of wood and promote the realization of sustainable use. In addition, cationic wood that has been saturated with microplastics can be prepared into a new composite board after hot pressing. This composite material can not only effectively utilize wood resources, but also give it new physical and chemical properties through hot pressing process while removing microplastics, and has potential market application value. In this way, the present invention not only solves the problem of microplastics in the field of environmental protection, but also opens up a new path for the reuse and sustainable development of wood. Summary of the invention
[0005] In view of the above-mentioned shortcomings, the present invention discloses a method for preparing a plastic wood-based filter material for removing microplastics in water. The prepared plastic wood-based filter material has good hydrophilicity and plasticity, and can effectively adsorb microplastics.
[0006] The present invention is achieved by adopting the following technical solutions: A method for preparing a plastic wood-based filter material for removing microplastics in water, comprising the following steps: (1) natural wood is placed in a treatment solution and treated at 100-105°C for 36-48 hours, then the wood is taken out and the remaining treatment solution is collected for standby use, the wood is soaked in water for 2-3 times to obtain wood from which lignin and surface colloid substances are removed, and then naturally air-dried for 30 hours to form a shrunken wood intermediate; the wood intermediate is immersed in water for 3 minutes to obtain flexible wood; the treatment solution includes the following components in concentrations: 2.5M sodium hydroxide and 0.4M sodium sulfite; (2) Add EPTMAC (2,3-epoxypropyltrimethylammonium chloride) to a 2 wt% sodium hydroxide solution to obtain a mixed solution, then place the flexible wood obtained in step (1) in a deionized water solution, then add the mixed solution and stir to mix, then place in an oil bath and stir at 80-90° C. for 5-8 hours, take out the wood and wash it with deionized water for 2-3 times, then air-dry it at room temperature for 30 hours to obtain a modified wood; the mass ratio of the flexible wood to EPTMAC is 1:(15-20); (3) taking the treated liquid described in step (1) and adding a 2M hydrochloric acid solution to adjust the pH value to 2, letting it stand and precipitating, and then filtering to obtain a suction filtration residue, washing the suction filtration residue with deionized water until it is neutral, and then drying it at 50°C for 48 hours to obtain lignin, dissolving lignin and o-phenylenediamine in an acid solution to obtain a mixed solution, reacting the mixed solution at 220°C for 10 hours to obtain a reaction solution, and then naturally cooling the reaction solution to room temperature, and then centrifuging it at 8000 r / min for 15 minutes, taking the supernatant and dialyzing it in deionized water for 48 hours to obtain a solution containing carbon dots, and drying the solution containing carbon dots at 70°C to obtain carbon dot powder; (4) The carbon dot powder obtained in step (3) is subjected to ultrasonic treatment, and then added to anhydrous ethanol to obtain a carbon dot ethanol solution, the carbon dot ethanol solution is evenly dropped onto the modified wood obtained in step (2), and then the modified wood is dried at 60°C for 20 min to obtain a plastic wood-based filter material.
[0007] The present invention significantly improves the hydrophilicity of the material by means of delignification, and effectively connects the pore structure inside the wood, thereby enhancing the plasticity of the wood. Then, the wood is modified with a cationic etherifying agent (EPTMAC) to obtain plastic cationized wood. After the adsorption material is prepared into a filter, combined with the design of a three-layer filter, efficient removal of micro-nano plastics is achieved. At the same time, for the plastic wood-based filter material (i.e., plastic cationized wood) that has been saturated with micro-nano plastics, a new laminate can be obtained after hot pressing. In this process, the micro-nano plastics act as an adhesive to effectively fill the fragile areas of the wood pores, significantly reducing the secondary pollution caused by the desorption of micro / nano plastics.
[0008] The synthesis process of this process is simple, and the raw materials are green and degradable. Pressing the wood after adsorbing pollutants into boards helps to improve the sustainable use value of the material. The present invention not only improves the effect of sewage treatment, but also provides an innovative idea for the utilization of renewable materials. The present invention uses EPTMAC to modify the flexible wood, reverses the Zeta potential of the wood surface, and significantly enhances its adsorption capacity for microplastics with opposite charges. The cationic flexible wood is tightly combined with microplastics in water through electrostatic effects, hydrogen bonds and π-π conjugation. At the same time, with the help of the three-layer filter, the micro-nano plastics in the water are effectively removed. This method not only improves the efficiency of sewage treatment, but also provides a feasible solution for industrial applications.
[0009] Furthermore, in step (1), the volume ratio of the mass of the natural wood to the treatment liquid is 2 g:100 mL.
[0010] Furthermore, in step (2), the stirring is carried out at a speed of 200 to 250 r / min.
[0011] Furthermore, in step (2), the mass ratio of the EPTMAC to the volume ratio of the sodium hydroxide solution is 15 g:100 mL.
[0012] Furthermore, in step (2), the moisture content of the modified wood is less than 8-10%.
[0013] Furthermore, in step (3), the mass ratio of lignin to o-phenylenediamine is 1:3, and the volume ratio of the mass of lignin to the acid solution is 1 g:100 mL.
[0014] Furthermore, in step (3), the acid solution is obtained by mixing equal volumes of a 40% sulfuric acid solution and phosphoric acid.
[0015] Furthermore, in step (4), the mass ratio of the carbon dot powder to the volume of anhydrous ethanol is 30 mg:1 mL.
[0016] The application of the plastic wood-based filter material is to use it to prepare a filter that can adsorb microplastics in water. Specifically, the plastic wood-based filter material is cut into block filter materials, and then more than three blocks of filter materials are stacked and placed in a chromatographic filter column to obtain the filter.
[0017] Furthermore, the spacing between adjacent filter materials is 1 to 2 cm.
[0018] Compared with the prior art, this technical solution has the following beneficial effects: 1. The present invention solves the problem of low adsorption efficiency and high cost for nanoplastic removal in the existing sewage treatment process, and also solves the problem of secondary pollution caused by the release of adsorbed micro-nanoplastics into the environment again. The present invention effectively removes lignin so that the material maintains the natural fiber structure of wood and forms a highly interconnected porous network. This interconnected porous structure provides abundant active sites for the adsorption of microplastics, significantly improves the internal water flow channels, promotes the efficient transmission of water molecules in the material, thereby accelerating the adsorption process and improving the overall treatment efficiency. In addition, by removing lignin from wood, a highly interconnected porous structure can be effectively generated and the water transmission capacity can be improved, the hydrophilicity can be improved, the contact opportunity between the adsorbent material and microplastics can be increased, the cationic surface modification can enhance the adsorption capacity of delignified wood for microplastics, and the microplastic / adsorbent composite material can be hot-pressed to form a higher strength wood-plastic composite material to prevent secondary pollution of microplastics.
[0019] 2. The adsorption and recovery of microplastics are key links in the prevention and control of pollutants in water. Currently, most microplastics are recovered by adsorption, but most adsorbents are in powder form, which limits their application in liquid flow systems. The present invention prepares the prepared plastic wood-based filter material (i.e., plastic cationized wood) into a filter so that microplastics can be effectively adsorbed in a flow device. The modified wood saturated with adsorbed microplastics is hot-pressed, and the adsorbed nanoplastic particles can be used as a strong adhesive for hot-pressed wood to enhance the mechanical properties of the wood.
[0020] 3. The use of wood-based materials is not only environmentally friendly, but also can enhance the adsorption capacity of microplastics by regulating its surface properties. Compared with traditional physical and chemical treatment methods, the plastic wood-based filter material (i.e., plastic cationized wood) prepared by the present invention can achieve rapid and efficient removal of microplastics while avoiding the risk of secondary pollution. The grafting of cationic groups makes it easier for microplastics to combine with flexible wood, greatly improving the adsorption performance of microplastics. Flexible wood can be optimized according to demand and adapted to water treatment scenarios of different scales, with good versatility and application potential. Therefore, the present invention provides an innovative, environmentally friendly and efficient solution to the problem of microplastic pollution in water.
[0021] 4. The present invention not only significantly improves the material's ability to adsorb microplastics, but also enhances its stability and applicability under different water quality conditions, so that it can effectively capture microplastics in a variety of water environments. Moreover, the cationic etherification modification method of the present invention has a wide range of applicability and can be efficiently applied to a variety of biomass-based materials, such as poplar, bamboo and rattan, thereby broadening the source of materials and improving their sustainability. The present invention achieves broad-spectrum adsorption of a variety of microplastics (including PS, PMMA, PVC) through electrostatic action, and exhibits high adsorption efficiency for microplastics of different sizes, while maintaining stable capture capabilities in different water environments, providing an environmentally friendly and efficient microplastic removal technology. In addition, for adsorbents that have reached a saturated state of adsorption of microplastics, the present invention provides a method for hot pressing treatment to obtain a sustainable sheet. This hot-pressed sheet not only improves the mechanical properties of the material, but also effectively reduces environmental pollution. BRIEF DESCRIPTION OF THE DRAWINGS
[0022] Figure 1 Schematic diagram of the device structure of the test method described in Experimental Example 1.
[0023] Figure 2 This is a data chart of the results obtained from testing different filter materials in Experimental Example 2, wherein 1 to 3 correspond to natural wood, delignified wood, and the plastic wood-based filter material of the present invention, respectively.
[0024] Figure 3 It is the fluorescence spectra of the solutions obtained after different samples were treated with microplastic solutions in Experimental Example 2, wherein curve 1 is the untreated microplastic solution, and curves 2 to 4 correspond to the solutions after treatment with sample 1, sample 2 and sample 3 respectively.
[0025] Figure 4 : is the SEM image of the natural wood described in Experimental Example 2 at a scale of 500um and 100um, wherein A is 500um and B is 100um.
[0026] Figure 5 This is a digital picture of the solution obtained after using different samples to treat the microplastic solution in Experimental Example 2, where bottle A is the untreated microplastic solution, and bottles B to D correspond to the solutions after treatment with sample 1, sample 2 and sample 3 respectively.
[0027] Figure 6 These are optical microscope images of the solutions obtained after using different samples to treat the microplastic solutions in Experimental Example 2, where A is the untreated microplastic solution, and B to D correspond to the solutions after treatment with Sample 1, Sample 2, and Sample 3, respectively.
[0028] Figure 72 is a graph showing the results of element content detection in different samples in Experimental Example 2, wherein curves 21 to 23 correspond to sample 1, sample 2, and sample 3, respectively, C represents carbon, N represents nitrogen, and O represents oxygen.
[0029] Figure 8 It is an SEM image of the plastic wood-based filter material after the adsorption test in Experimental Example 3, wherein A is the plastic wood-based filter material adsorbing polystyrene plastic particles with a particle size of 1um, and the scale is 50.0um; B is the plastic wood-based filter material adsorbing polystyrene plastic particles with a particle size of 1um, and the scale is 20.0um; C is the plastic wood-based filter material adsorbing polystyrene plastic particles with a particle size of 500nm, and the scale is 50.0um; D is the plastic wood-based filter material adsorbing polystyrene plastic particles with a particle size of 500nm, and the scale is 20.0um. DETAILED DESCRIPTION
[0030] The present invention is further described by the following examples, but is not intended to be limiting of the present invention. Specific experimental conditions and methods not specified in the following examples are conventional methods commonly known to those skilled in the art.
[0031] Example 1: A method for preparing a plastic wood-based filter material for removing microplastics in water, comprising the following steps: (1) Natural wood is placed in a treatment solution and treated at 102°C for 48 hours, then the wood is taken out and the remaining treatment solution is collected for later use, the wood is soaked in water for 3 times to obtain wood from which lignin and surface colloid substances are removed, and then naturally air-dried for 30 hours to form a shrunken wood intermediate; the wood intermediate is immersed in water for 3 minutes to obtain flexible wood; the treatment solution includes the following components in concentrations: 2.5M sodium hydroxide and 0.4M sodium sulfite; the mass ratio of the natural wood to the volume of the treatment solution is 2g:100mL; (2) EPTMAC (2,3-epoxypropyltrimethylammonium chloride) is added to a sodium hydroxide solution with a concentration of 2 wt% to obtain a mixed solution, and then the flexible wood obtained in step (1) is placed in a deionized water, and then the mixed solution is added and stirred at a speed of 220 r / min, and then placed in an oil bath and stirred at 85° C. for 6 h, the wood is taken out and washed with deionized water for 3 times, and then air-dried at room temperature for 30 h to obtain a modified wood; the mass ratio of the flexible wood to EPTMAC is 1:16; the mass ratio of the EPTMAC to the sodium hydroxide solution is 15 g:100 mL; (3) The treated liquid in step (1) is added with a 2M hydrochloric acid solution to adjust the pH value to 2, and the mixture is filtered to obtain a suction residue after standing and settling. The suction residue is washed with deionized water until neutral and then dried at 50°C for 48 hours to obtain lignin. The lignin and o-phenylenediamine are dissolved in an acid solution to obtain a mixed solution. The mixed solution is reacted at 220°C for 10 hours to obtain a reaction solution. The reaction solution is then naturally cooled to room temperature, and then centrifuged at 8000 r / min for 15 minutes. The supernatant is dialyzed in deionized water for 48 hours to obtain a solution containing carbon dots. The solution containing carbon dots is dried at 70°C to obtain a carbon dot powder. The mass ratio of lignin to o-phenylenediamine is 1:3, and the mass ratio of the lignin to the acid solution is 1 g:100 mL. The acid solution is obtained by mixing equal volumes of a 40% sulfuric acid solution and phosphoric acid. (4) The carbon dot powder obtained in step (3) is subjected to ultrasonic treatment, and then added to anhydrous ethanol to obtain a carbon dot ethanol solution, the carbon dot ethanol solution is uniformly dropped onto the modified wood obtained in step (2), and then the modified wood is dried at 60°C for 20 min to obtain a plastic wood-based filter material; the mass ratio of the carbon dot powder to the volume of anhydrous ethanol is 30 mg:1 mL.
[0032] The application of the plastic wood-based filter material described in this embodiment is to use it to prepare a filter that can adsorb microplastics in water. Specifically, the plastic wood-based filter material is cut into block filter materials, and then three blocks of filter materials are stacked and placed in a chromatographic filter column to obtain the filter; the spacing between adjacent filter materials is 1.5 cm.
[0033] Example 2: A method for preparing a plastic wood-based filter material for removing microplastics in water, comprising the following steps: (1) Natural wood is placed in a treatment solution and treated at 100°C for 48 hours, then the wood is taken out and the remaining treatment solution is collected for standby use, the wood is soaked in water twice to obtain wood from which lignin and surface colloid substances are removed, and then naturally air-dried for 30 hours to form a shrunken wood intermediate; the wood intermediate is immersed in water for 3 minutes to obtain flexible wood; the treatment solution includes the following components in concentrations: 2.5M sodium hydroxide and 0.4M sodium sulfite; the mass ratio of the natural wood to the volume of the treatment solution is 2g:100mL; (2) EPTMAC (2,3-epoxypropyltrimethylammonium chloride) is added to a sodium hydroxide solution with a concentration of 2 wt% to obtain a mixed solution, and then the flexible wood obtained in step (1) is placed in a deionized water, and then the mixed solution is added and stirred at a speed of 200 r / min, and then placed in an oil bath and stirred at 80° C. for 8 h, the wood is taken out and washed twice with deionized water, and then air-dried at room temperature for 30 h to obtain a modified wood; the mass ratio of the flexible wood to EPTMAC is 1:15; the mass ratio of the EPTMAC to the sodium hydroxide solution is 15 g:100 mL; (3) The treated liquid in step (1) is added with a 2M hydrochloric acid solution to adjust the pH value to 2, and the mixture is filtered to obtain a suction residue after standing and settling. The suction residue is washed with deionized water until neutral and then dried at 50°C for 48 hours to obtain lignin. The lignin and o-phenylenediamine are dissolved in an acid solution to obtain a mixed solution. The mixed solution is reacted at 220°C for 10 hours to obtain a reaction solution. The reaction solution is then naturally cooled to room temperature, and then centrifuged at 8000 r / min for 15 minutes. The supernatant is dialyzed in deionized water for 48 hours to obtain a solution containing carbon dots. The solution containing carbon dots is dried at 70°C to obtain a carbon dot powder. The mass ratio of lignin to o-phenylenediamine is 1:3, and the mass ratio of the lignin to the acid solution is 1 g:100 mL. The acid solution is obtained by mixing equal volumes of a 40% sulfuric acid solution and phosphoric acid. (4) The carbon dot powder obtained in step (3) is subjected to ultrasonic treatment, and then added to anhydrous ethanol to obtain a carbon dot ethanol solution, the carbon dot ethanol solution is uniformly dropped onto the modified wood obtained in step (2), and then the modified wood is dried at 60°C for 20 min to obtain a plastic wood-based filter material; the mass ratio of the carbon dot powder to the volume of anhydrous ethanol is 30 mg:1 mL.
[0034] The application of the plastic wood-based filter material described in this embodiment is to use it to prepare a filter that can adsorb microplastics in water. Specifically, the plastic wood-based filter material is cut into block filter materials, and then three blocks of filter materials are stacked and placed in a chromatographic filter column to obtain the filter; the spacing between adjacent filter materials is 1 cm.
[0035] Example 3: A method for preparing a plastic wood-based filter material for removing microplastics in water, comprising the following steps: (1) Natural wood is placed in a treatment solution and treated at 104°C for 40 hours, then the wood is taken out and the remaining treatment solution is collected for later use, the wood is soaked in water for 3 times to obtain wood from which lignin and surface colloid substances are removed, and then naturally air-dried for 30 hours to form a shrunken wood intermediate; the wood intermediate is immersed in water for 3 minutes to obtain flexible wood; the treatment solution includes the following components in concentrations: 2.5M sodium hydroxide and 0.4M sodium sulfite; the mass ratio of the natural wood to the volume of the treatment solution is 2g:100mL; (2) EPTMAC (2,3-epoxypropyltrimethylammonium chloride) is added to a sodium hydroxide solution with a concentration of 2 wt% to obtain a mixed solution, and then the flexible wood obtained in step (1) is placed in a deionized water, and then the mixed solution is added and stirred at a speed of 250 r / min, and then placed in an oil bath and stirred at 88° C. for 7 h, the wood is taken out and washed with deionized water for 3 times, and then air-dried at room temperature for 30 h to obtain a modified wood; the mass ratio of the flexible wood to EPTMAC is 1:18; the mass ratio of the EPTMAC to the sodium hydroxide solution is 15 g:100 mL; (3) The treated liquid in step (1) is added with a 2M hydrochloric acid solution to adjust the pH value to 2, and the mixture is filtered to obtain a suction residue after standing and settling. The suction residue is washed with deionized water until neutral and then dried at 50°C for 48 hours to obtain lignin. The lignin and o-phenylenediamine are dissolved in an acid solution to obtain a mixed solution. The mixed solution is reacted at 220°C for 10 hours to obtain a reaction solution. The reaction solution is then naturally cooled to room temperature, and then centrifuged at 8000 r / min for 15 minutes. The supernatant is dialyzed in deionized water for 48 hours to obtain a solution containing carbon dots. The solution containing carbon dots is dried at 70°C to obtain a carbon dot powder. The mass ratio of lignin to o-phenylenediamine is 1:3, and the mass ratio of the lignin to the acid solution is 1 g:100 mL. The acid solution is obtained by mixing equal volumes of a 40% sulfuric acid solution and phosphoric acid. (4) The carbon dot powder obtained in step (3) is subjected to ultrasonic treatment, and then added to anhydrous ethanol to obtain a carbon dot ethanol solution, the carbon dot ethanol solution is uniformly dropped onto the modified wood obtained in step (2), and then the modified wood is dried at 60°C for 20 min to obtain a plastic wood-based filter material; the mass ratio of the carbon dot powder to the volume of anhydrous ethanol is 30 mg:1 mL.
[0036] The application of the plastic wood-based filter material described in this embodiment is to use it to prepare a filter that can adsorb microplastics in water. Specifically, the plastic wood-based filter material is cut into block filter materials, and then three blocks of filter materials are stacked and placed in a chromatographic filter column to obtain the filter; the spacing between adjacent filter materials is 1.5 cm.
[0037] Example 4: A method for preparing a plastic wood-based filter material for removing microplastics in water, comprising the following steps: (1) Natural wood is placed in a treatment solution and treated at 105°C for 36 hours, then the wood is taken out and the remaining treatment solution is collected for later use, the wood is soaked in water twice to obtain wood from which lignin and surface colloid substances are removed, and then naturally air-dried for 30 hours to form a shrunken wood intermediate; the wood intermediate is immersed in water for 3 minutes to obtain flexible wood; the treatment solution includes the following components in concentrations: 2.5M sodium hydroxide and 0.4M sodium sulfite; the mass ratio of the natural wood to the volume of the treatment solution is 2g:100mL; (2) EPTMAC (2,3-epoxypropyltrimethylammonium chloride) is added to a sodium hydroxide solution with a concentration of 2 wt% to obtain a mixed solution, and then the flexible wood obtained in step (1) is placed in a deionized water, and then the mixed solution is added and stirred at a speed of 250 r / min, and then placed in an oil bath and stirred at 90° C. for 5 h, the wood is taken out and washed with deionized water for 2 to 3 times, and then air-dried at room temperature for 30 h to obtain a modified wood; the mass ratio of the flexible wood to EPTMAC is 1:20; the mass ratio of the EPTMAC to the sodium hydroxide solution is 15 g:100 mL; (3) The treated liquid in step (1) is added with a 2M hydrochloric acid solution to adjust the pH value to 2, and the mixture is filtered to obtain a suction residue after standing and settling. The suction residue is washed with deionized water until neutral and then dried at 50°C for 48 hours to obtain lignin. The lignin and o-phenylenediamine are dissolved in an acid solution to obtain a mixed solution. The mixed solution is reacted at 220°C for 10 hours to obtain a reaction solution. The reaction solution is then naturally cooled to room temperature, and then centrifuged at 8000 r / min for 15 minutes. The supernatant is dialyzed in deionized water for 48 hours to obtain a solution containing carbon dots. The solution containing carbon dots is dried at 70°C to obtain a carbon dot powder. The mass ratio of lignin to o-phenylenediamine is 1:3, and the mass ratio of the lignin to the acid solution is 1 g:100 mL. The acid solution is obtained by mixing equal volumes of a 40% sulfuric acid solution and phosphoric acid. (4) The carbon dot powder obtained in step (3) is subjected to ultrasonic treatment, and then added to anhydrous ethanol to obtain a carbon dot ethanol solution, the carbon dot ethanol solution is uniformly dropped onto the modified wood obtained in step (2), and then the modified wood is dried at 60°C for 20 min to obtain a plastic wood-based filter material; the mass ratio of the carbon dot powder to the volume of anhydrous ethanol is 30 mg:1 mL.
[0038] The application of the plastic wood-based filter material described in this embodiment is to use it to prepare a filter that can adsorb microplastics in water. Specifically, the plastic wood-based filter material is cut into block filter materials, and then three blocks of filter materials are stacked and placed in a chromatographic filter column to obtain the filter; the spacing between adjacent filter materials is 2 cm.
[0039] Experimental Example 1: A natural wood sample with a size of 3 mm x 3 cm x 3 cm was taken as a sample, and a plastic wood-based filter material was prepared according to the method described in Examples 1 to 4, and then Figure 1 As shown, the plastic wood-based filter material is cut into block filter materials, and then three pieces of the filter materials are stacked together and placed in a chromatographic filter column. Then, the polystyrene solution is diluted to 350 mg / L with deionized water and the pH is about neutral. The polystyrene solution is slowly poured from the top of the chromatographic filter column, and the solution flows down from the wood pores, and the micro-nano plastics are adsorbed on the plastic wood-based filter material.
[0040] Flow cytometer and fluorescence spectrophotometer were used to detect the residual microplastic content in the solution, and the removal rate and adsorption capacity of polystyrene were calculated. The specific results are shown in Table 1.
[0041] Table 1 Test results of microplastic adsorption by plastic wood-based filter materials prepared by the method of the present invention
[0042] It can be seen from the data in Table 1 that the plastic wood-based filter material prepared by the method of the present invention has good adsorption performance for microplastics.
[0043] Experimental Example 2: Take natural wood as sample 1, take delignified wood prepared according to step (1) of the method described in Example 2 as sample 2, take plastic wood-based filter material prepared according to the method described in Example 2 as sample 3, and test samples 1 to 3 according to the method described in Experimental Example 1 to calculate the removal rate of polystyrene. For specific results, see Figure 2 and Figure 3 , and the photos of the solutions after different sample treatments can be found in Figures 5-6 The pore structure of the natural wood is shown in Figure 4 , the element content test results of different samples are shown in Figure 7 .
[0044] according to Figure 2 and Figure 3 As shown, the plastic wood-based filter material prepared by the method of the present invention has a better microplastic removal rate than natural wood and delignified wood; according to Figure 7 It can be seen that the nitrogen content in the plastic wood-based filter material prepared by the method of the present invention is significantly increased, indicating that the cationic modification method adopted by the present invention is successful.
[0045] Experimental Example 3: A natural wood sample with a size of 3 mm x 3 cm x 3 cm was taken as a sample, and a plastic wood-based filter material was prepared according to the method described in Example 1, and then Figure 1 As shown, the plastic wood-based filter material is cut into block filter materials, and three blocks of the filter materials are stacked together and placed in a chromatography filter column; at the same time, two test solutions are prepared using polystyrene plastic particles of two sizes, 1um and 500nm, with a concentration of 350mg / L and a neutral pH. After being treated with the plastic wood-based filter material, the SEM image obtained by testing the plastic wood-based filter material is shown in Figure 8 .according to Figure 8 It can be seen that the plastic wood-based filter material prepared by the present invention can effectively adsorb microplastic particles of different sizes.
[0046] Experimental Example 4: Take delignified wood, the plastic wood-based filter material described in the embodiment, and the plastic wood-based filter material after the adsorption test in Experimental Example 1, and the plastic wood-based filter material is saturated with polystyrene adsorption, and then use a hot press to hot press the above materials at a pressure of 5 MPa and a temperature of 200°C for 5 minutes, and then test the mechanical properties of the obtained hot-pressed materials. The specific results are shown in Table 2.
[0047] Table 2 Mechanical properties test results of materials
[0048] It can be seen from the data in Table 2 that the plastic wood-based filter material prepared by the present invention has excellent mechanical properties after being saturated with microplastics and formed into a board by hot pressing.
[0049] In addition, it should be understood that although the present specification is described according to implementation modes, not every implementation mode contains only one independent technical solution. This description of the specification is only for the sake of clarity. Those skilled in the art should regard the specification as a whole. The technical solutions in each embodiment may also be appropriately combined to form other implementation modes that can be understood by those skilled in the art.
Claims
1. A method for preparing a plastic wood-based filter material for removing microplastics in water, characterized in that: The following steps are involved: (1) natural wood is placed in a treatment solution and treated at 100-105°C for 36-48 hours, then the wood is taken out and the remaining treatment solution is collected for standby use, the wood is soaked in water for 2-3 times to obtain wood from which lignin and surface colloid substances are removed, and then naturally air-dried for 30 hours to form a shrunken wood intermediate; the wood intermediate is immersed in water for 3 minutes to obtain flexible wood; the treatment solution includes the following components in concentrations: 2.5M sodium hydroxide and 0.4M sodium sulfite; (2) EPTMAC is added to a 2 wt% sodium hydroxide solution to obtain a mixed solution, the flexible wood obtained in step (1) is then placed in a deionized water solution, and then the mixed solution is added and stirred, and then placed in an oil bath and stirred at 80 to 90° C. for 5 to 8 hours, the wood is taken out and washed with deionized water for 2 to 3 times, and then air-dried at room temperature for 30 hours to obtain a modified wood; the mass ratio of the flexible wood to EPTMAC is 1:(15 to 20); (3) taking the treated liquid described in step (1) and adding a 2M hydrochloric acid solution to adjust the pH value to 2, letting it stand and precipitating, and then filtering to obtain a suction filtration residue, washing the suction filtration residue with deionized water until it is neutral, and then drying it at 50°C for 48 hours to obtain lignin, dissolving lignin and o-phenylenediamine in an acid solution to obtain a mixed solution, reacting the mixed solution at 220°C for 10 hours to obtain a reaction solution, and then naturally cooling the reaction solution to room temperature, and then centrifuging it at 8000 r / min for 15 minutes, taking the supernatant and dialyzing it in deionized water for 48 hours to obtain a solution containing carbon dots, and drying the solution containing carbon dots at 70°C to obtain carbon dot powder; (4) The carbon dot powder obtained in step (3) is subjected to ultrasonic treatment, and then added to anhydrous ethanol to obtain a carbon dot ethanol solution, the carbon dot ethanol solution is evenly dropped onto the modified wood obtained in step (2), and then the modified wood is dried at 60°C for 20 min to obtain a plastic wood-based filter material.
2. The method for preparing a plastic wood-based filter material for removing microplastics in water according to claim 1, characterized in that: In step (1), the volume ratio of the mass of the natural wood to the treatment liquid is 2 g:100 mL.
3. The method for preparing a plastic wood-based filter material for removing microplastics in water according to claim 1, characterized in that: In step (2), the stirring is carried out at a speed of 200 to 250 r / min.
4. The method for preparing a plastic wood-based filter material for removing microplastics in water according to claim 1, characterized in that: In step (2), the mass ratio of the EPTMAC to the volume ratio of the sodium hydroxide solution is 15 g:100 mL.
5. The method for preparing a plastic wood-based filter material for removing microplastics in water according to claim 1, characterized in that: In step (2), the moisture content of the modified wood is less than 8-10%.
6. The method for preparing a plastic wood-based filter material for removing microplastics in water according to claim 1, characterized in that: In step (3), the mass ratio of lignin to o-phenylenediamine is 1:3, and the volume ratio of the mass of lignin to the acid solution is 1 g:100 mL.
7. The method for preparing a plastic wood-based filter material for removing microplastics in water according to claim 1, characterized in that: In step (3), the acid solution is obtained by mixing equal volumes of a 40% sulfuric acid solution and phosphoric acid.
8. The method for preparing a plastic wood-based filter material for removing microplastics in water according to claim 1, characterized in that: In step (4), the mass ratio of the carbon dot powder to the volume of anhydrous ethanol is 30 mg:1 mL.
9. The use of the plastic wood-based filter material according to any one of claims 1 to 8, characterized in that: The plastic wood-based filter material is used to prepare a filter that can adsorb microplastics in water. Specifically, the plastic wood-based filter material is cut into block filter materials, and then more than three blocks of filter materials are stacked and placed in a chromatographic filter column to obtain the filter.
10. The use of the plastic wood-based filter material according to claim 9, characterized in that: The spacing between adjacent filter materials is 1 to 2 cm.
Citation Information
Cited By
Method for efficiently removing micro-nano plastic of PVC in water body by multi-nitrogen wood powder
CN122725420A